Parenting Programs in Shelby County, Tennessee A Brief Review of the Research Literature - Auger, Anamarie (RAND Corporation, 2016)
Programs that serve parents of young children provide families with services in order to improve parenting practices and positively influence children's development. This report presents an overview of outcomes associated with rigorously evaluated parenting programs currently operating in Shelby County, Tennessee.